Pelatihan Pelatihan Mendesain Media Pembelajaran Berbasis Teknologi untuk Guru-Guru di Sekolah Dasar - Evi Rizqi Salamah; Desty Dwi Rochmania; Muhammad Yusuf Effendi; Zuni Eka Tiyas Rifayanti (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This community service activity aims to enhance the competence of elementary school teachers in designing innovative and engaging learning media that are aligned with the needs of 21st-century learners. This activity was motivated by the limited ability of teachers to utilize digital technology as a learning medium, while the implementation of the Merdeka Curriculum requires creative, interactive, and student-centered learning approaches. Based on the Cognitive Theory of Multimedia Learning, the use of digital learning media that integrates visual and interactive elements can improve students’ motivation and understanding during the learning process. However, the main challenges faced by teachers include limited technological skills and a lack of creativity in developing interactive learning media. The training was conducted through several stages, including socialization, theoretical and practical training on media design using simple digital applications such as Canva, interactive PowerPoint, and Liveworksheet, as well as assistance in developing learning media products. The activity was carried out over two days using lecture, demonstration, and hands-on practice methods. The results showed a significant improvement in teachers’ skills and understanding in designing contextual and engaging digital learning media. The teachers also demonstrated high enthusiasm and commitment to implementing the outcomes of the training in classroom learning activities. Therefore, this program contributed positively to improving the quality of learning in elementary schools.